2021
DOI: 10.1002/ente.202001012
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Gas Diffusion Layer Porosity Distribution on Proton Exchange Membrane Fuel Cell

Abstract: Figure 4. Fuel cell polarization curves of different porosity models.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 30 publications
2
10
0
Order By: Relevance
“…140 Although reducing porosity can enhance the conductivity of the electrode, it also hinders the transmission of gas. 141 In addition, the porosity distribution also seriously affects the uniform distribution of reaction gas and current density within the catalytic layer. Therefore, it is necessary to gradient design the porosity of the GDLs.…”
Section: Gas Diffusion Layers (Gdls) In Pemfcs With High Specific Pow...mentioning
confidence: 99%
“…140 Although reducing porosity can enhance the conductivity of the electrode, it also hinders the transmission of gas. 141 In addition, the porosity distribution also seriously affects the uniform distribution of reaction gas and current density within the catalytic layer. Therefore, it is necessary to gradient design the porosity of the GDLs.…”
Section: Gas Diffusion Layers (Gdls) In Pemfcs With High Specific Pow...mentioning
confidence: 99%
“…They concluded that the GDL with a logarithmically decreasing porosity gradient improved the cell performance. Yang et al [ 29 ] numerically analyzed the effects of GDL porosity variation with various increasing gradients from the gas inlet to the outlet, they concluded that a cell with an increasing porosity gradient could increase the current density. Sim et al [ 30 ] achieved a non-uniform porosity distribution by changing the compression ratio of the GDL, the outlet area was less compressed than the inlet area and hence had a larger porosity, and the cell performance increased.…”
Section: Introductionmentioning
confidence: 99%
“…Proton exchange membrane fuel cell (PEMFC) has been widely considered as an alternative power source for electric vehicles, regional power stations, and mobile power due to its advantages of zero-emission, fast start-up, and high-energy efficiency. [1][2][3][4] The proton exchange membrane (PEM) is a core component of PEMFC, which plays a key role in separating reaction gas and providing proton transfer channels. [5] A low-temperature fuel cell places high demands on the PEM, including: 1) high proton conductivity; 2) low water and fuel permeation, and 3) long-term mechanical, thermal, and acidic stability.…”
Section: Introductionmentioning
confidence: 99%